Too many cooks spoil the broth? Number of promotional gifts and impact on consumer choice. (November 2022) - Kumari, Rashmi; Tatavarthy, Aruna Divya; Sahay, Arvind
Abstract: As an alternative to traditional free-gift promotions where consumers have little say over which gift item they receive, retailers are increasingly offering consumers an option to choose from a menu of free-gift items (e.g., buy a washing machine and pick a steam iron or a vacuum cleaner for free). However, little is known about what drives consumers' perceptions of value associated with a menu of free-gift items. Using data from a unique retail-promotion setting and controlled-lab studies, we show that the perceived attractiveness of free-gifts follows an inverted U-shape (or plateauing-shape) as the 'menu-size' increases. We also highlight the interplay of resource (time and money) constraints experienced by consumers and menu-size on the proposed effects. Our findings not only help retailers better design free-gift promotions but also contribute to the academic conversations in the domain of promotional-gifts by exploring the downstream consequences of offering choices in a promotional-gift context.